Long Non-coding RNA FIRRE Acts as a miR-520a-3p Sponge to Promote Gallbladder Cancer Progression via Mediating YOD1 Expression - Wang, Shuqing; Wang, Yang; Wang, Shouhua; Tong, Huanjun; Tang, Zhaohui; Wang, Jiandong; Zhang, Yongjie; Ou, Jingmin; Quan, Zhiwei (Frontiers in Genetics, 2021)
Objectives: The role of lncRNAs in gallbladder cancer (GBC) remains poorly understood. In this study, we explored the function of FIRRE in GBC. Materials and Methods: Whole transcriptome resequencing was performed in 3 pairs of GBC tissues and adjacent non-tumor tissues. lncRNA FIRRE expression was verified by real-time PCR. The function of FIRRE in GBC was evaluated by experiments in vitro and in vivo. The mechanism of FIRRE was investigated via fluorescent in situ hybridization, RNA pull-down, dual luciferase reporter assays and RNA immunoprecipitation. Results: FIRRE level was dramatically increased in GBC tissues compared to that in the adjacent non-tumor tissues. High expression of FIRRE was closely related to clinical stage and poor prognosis in GBC patients. Moreover, FIRRE remarkably enhanced proliferation, migration and inhibited apoptosis of GBC cells. Mechanistically, FIRRE modulated YOD1 expression by sponging miR-520a-3p, thus contributing to the development of GBC. Conclusions: Our data revealed that FIRRE might act as a novel mediator in GBC progression by sponging miR-520a-3p and regulating YOD1. FIRRE might be regarded as the potential diagnostic marker or target for GBC treatment.